Cavafy hero: literary appropriations and cultural projections of the poet in English and American literature - Dimirouli, F (2014)
The present thesis examines the way E.M. Forster, Lawrence Durrell, W.H. Auden, Stephen Spender, Joseph Brodsky, and James Merrill appropriated C.P. Cavafy in writings that were disseminated and consumed amongst culturally dominant literary circles, and which eventually determined the Greek-Alexandrian poet’s international reputation. I aim to contribute a new perspective on Cavafy, by evading the text-based tradition of reception studies, and proposing an alternative method of discussing the production of Cavafy's canonical status. Inspired by Pierre Bourdieu's sociological theory, I view literary canonization as involving a variety of factors at play beyond creative achievement: in particular, relationships of 'authorial consecration' whereby writers create and circulate cultural capital through their power to legitimize other artists. The critical and fictional texts I analyse perform readings of Cavafy's poetry alongside imaginative portrayals of the poet's life and personality. I take this complementary relationship - between the image of the poet each author projects and their reading of his work - as a starting point to explore the broader ideas of aesthetics and authorial subjectivity that inform the renderings of Cavafy generated by prominent literary figures. Rather than passive recipients of influence, these figures are considered as active agents in the production of 'Cavafy narratives', appropriating the poet according to their own agendas, while also projecting onto him their own position within the cultural field. Eventually, Cavafy becomes a point of insight into the multiplicity of networks and practices involved in the production of cultural currency; in turn, the study of the construction of Cavafy's authorial identity sheds light on the cumulative processes that have defined the way the poet is read and perceived to the present day. This duality of perspective is essential to a study concerned with the cultural contexts framing the poet's steady rise to international fame throughout the 20th century.